2017
DOI: 10.1186/s13034-017-0163-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential therapeutic effects of atomoxetine and methylphenidate in childhood attention deficit/hyperactivity disorder as measured by near-infrared spectroscopy

Abstract: BackgroundThe stimulant methylphenidate (MPH) and the nonstimulant atomoxetine (ATX) are the most commonly-prescribed pharmacological treatments for attention deficit/hyperactivity disorder (ADHD). However, the drug-specific mechanism of action on brain function in ADHD patients is not well known. This study examined differences in prefrontal hemodynamic activity between MPH and ATX in children with ADHD as measured by near-infrared spectroscopy (NIRS) using the Stroop color-word task.MethodsThirty children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 68 publications
1
18
2
Order By: Relevance
“…From the point of view of medication, it has been suggested that atomoxetine (frequently used as second-line medication) may be more effective in reducing impulsivity than is the case for methylphenidate (first-line treatment), which may in turn be more beneficial in terms of reducing inattention [76,77]. Importantly, only atomoxetine has been shown to increase prefrontal activation during a Stroop task [78]. This effect may however crucially depend on different demographic factors and on individual differences in symptom severity [78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of medication, it has been suggested that atomoxetine (frequently used as second-line medication) may be more effective in reducing impulsivity than is the case for methylphenidate (first-line treatment), which may in turn be more beneficial in terms of reducing inattention [76,77]. Importantly, only atomoxetine has been shown to increase prefrontal activation during a Stroop task [78]. This effect may however crucially depend on different demographic factors and on individual differences in symptom severity [78].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, only atomoxetine has been shown to increase prefrontal activation during a Stroop task [78]. This effect may however crucially depend on different demographic factors and on individual differences in symptom severity [78]. Taken together, this suggests that it may indeed be very useful to take the individual pattern of cognitive deficits into account when developing treatment recommendations for individual patients [79].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, after administration of MPH and atomoxetine, the hemodynamic activity of the right PFC was increased, and the right hemisphere was lateralized. Meanwhile, in the study by Nakanishi et al [ 22 ], there was no statistically significant change in hemodynamic changes after MPH administration. Studies by Nakanishi et al [ 22 ] and Sanefuji et al [ 23 ] found contradictory results from other studies [ 19 - 21 , 24 ], such as left-lateralized effect after pharmacotherapy.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 95%
“…Meanwhile, in the study by Nakanishi et al [ 22 ], there was no statistically significant change in hemodynamic changes after MPH administration. Studies by Nakanishi et al [ 22 ] and Sanefuji et al [ 23 ] found contradictory results from other studies [ 19 - 21 , 24 ], such as left-lateralized effect after pharmacotherapy. The results may differ depending on the research and statistical method; therefore, future research is needed to confirm consistent results.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 95%
“…Altogether, 23 right-handed Korean children with ADHD (age range, 7–16 years; mean age, 9.96 ± 2.82) and 12 healthy control (HC) children (age range, 7–14 years; mean age, 11.33 ± 2.93) participated in this study. The number of participants required for adequate statistical power was based on previous studies that investigated drug effects in ADHD patients through fNIRS ( 23 , 40 42 ) and a previous study that described the optimal design for functional brain imaging ( 43 ). The detailed demographic and clinical characteristics of subjects are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%